Pendidikan Kesehatan Dalam Pencegahan Penyalahgunaan Napza Di Kalangan Pelajar SMA Negeri 4 Kotamobagu - Nurlela Hi Baco (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
The rise of drug abuse among students has received serious attention from all parties because it is damaging the nation's future generations. Drugs are very dangerous for anyone who consumes or uses them either by trial and error or due to an element of intent, if used excessively, these substances or materials can have very harmful consequences physically and mentally and lead to addiction. The purpose of this activity is expected to be able to provide understanding and awareness for students to avoid drug abuse and its bad effects. This activity was held in February 2023 at Kotamobagu State High School which was attended by 35 students. The activity was carried out using counseling, socialization and discussion methods using media in the form of PPT and distribution of leaflets directly to the students who attended. This activity resulted in a better understanding of students about the dangers of drug use.